2016
DOI: 10.1097/sla.0000000000001407
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes From Minimal Access Retroperitoneal and Open Pancreatic Necrosectomy in 394 Patients With Necrotizing Pancreatitis

Abstract: Increasing experience and advances in perioperative care have led to improvement in outcomes. The role of MARPN in reducing complications and deaths within a multimodality approach remains substantial and should be used initially if feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 48 publications
1
75
0
3
Order By: Relevance
“…This meta-analysis, however, suffered from significant heterogeneity. Another single-centre study compared 274 patients undergoing minimally invasive surgical necrosectomy with 120 patients undergoing open necrosectomy; mortality was 15% vs 23% (p=0.06) 12. Our study, with individual patient data, differed from these earlier studies because of its much larger sample size, and as a consequence the possibility to analyse different risk groups and to adjust for the effects of confounding and selection bias.…”
Section: Discussionmentioning
confidence: 89%
“…This meta-analysis, however, suffered from significant heterogeneity. Another single-centre study compared 274 patients undergoing minimally invasive surgical necrosectomy with 120 patients undergoing open necrosectomy; mortality was 15% vs 23% (p=0.06) 12. Our study, with individual patient data, differed from these earlier studies because of its much larger sample size, and as a consequence the possibility to analyse different risk groups and to adjust for the effects of confounding and selection bias.…”
Section: Discussionmentioning
confidence: 89%
“…The traditional approach is open necrosectomy with closed packing,16 repeat debridement (Figure 1), or continuous lavage. Modern alternatives include laparoscopic transperitoneal necrosectomy,17 video-assisted retroperitoneal debridement (VARD) (Figure 2),18 endoscopic necrosectomy,19 percutaneous drainage, and step-up or hybrid approaches 20,21…”
Section: Minimize Invasivenessmentioning
confidence: 99%
“…The treatment of PFCs has evolved considerably over the past decade, moving from what was once open surgical management to increasingly minimally invasive techniques, both by surgery and by endoscopy. High rates of complications (64%–95%) and mortality (15%–40%) with surgical treatment of PFCs has spurred the increasing adoption of endoscopic techniques for PFC drainage and debridement [1]. Randomized controlled trials (RCT) have confirmed that an endoscopic approach is safer and associated with lower costs, shorter hospital stay and improved quality of life compared to surgery [2].…”
Section: Introductionmentioning
confidence: 99%